Dental implants three-dimensional position affected by late facial bone growth: follow-up of 12 to 15 years - Ottoni, Judith; Gabriella, Márcia (Journal of Osseointegration, 2011)
Background The three-dimensional (3D) position of the osseointegrated dental implants provides favorable esthetical results and preserves the surrounding soft and hard tissues architecture in a long term analysis. However, recent studies demonstrate that the continued growth at adult life can also be noticed on the craniofacial skeleton. Therefore, considerable change may occur interfering on the relationship between a fix structure, the implant, and the adjacent teeth, with the possibility of forward and downward movement, due to the craniofacial growth. The question is: how long the harmonic relationship, previously established between the crown supported implant and natural teeth, is going to maintain esthetically pleasant? This article is based on three cases of adult patients with ages varying from 38 to 60 years old, when implants were inserted, and afterwards these patients were followed up during 12 to 15 years. It has been concluded that the continued craniofacial growth can lead to an infraocclusion of the implants-supported crown and to diasthem, which may negatively impact on both the aesthetics and the chewing quality.